2021
DOI: 10.1002/anie.202014501
|View full text |Cite
|
Sign up to set email alerts
|

The Electron Transfer Process in Mixed Valence Compounds with a Low‐lying Energy Bridge in Different Oxidation States

Abstract: Mixed‐valence compounds with the iso‐cyanidometal‐ligand bridge in different oxidation states are used as models for the investigation of the electron‐transfer process. We synthesized a series of trimetallic isocyanidometal‐bridged compounds with [Fe–CN–Ru–NC–Fe]n+ (n=2–4), in which the one‐electron oxidation product (N3+) and two‐electron oxidation product (N4+) compounds possess an isocyanidometal bridge whose energy is, respectively lower and slightly higher than the terminal metal centers energies. For the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 80 publications
4
40
0
Order By: Relevance
“…The similar phenomena has been reported by our previous work. [23] In addition, the energy of MM'CT for the three two-electron oxidation complexes decreases in the order of 4 . Moreover, the energy of MM'CT for N[PF 6 ] 4 (N = 1, 2, 3) are solvent independent which can be found from Figure S18 and Table S10, implying that the three two-electron oxidation complexes may belong to Class II-III or Class III mixed valence complexes.…”
Section: Uv-vis-nir Spectroscopymentioning
confidence: 99%
“…The similar phenomena has been reported by our previous work. [23] In addition, the energy of MM'CT for the three two-electron oxidation complexes decreases in the order of 4 . Moreover, the energy of MM'CT for N[PF 6 ] 4 (N = 1, 2, 3) are solvent independent which can be found from Figure S18 and Table S10, implying that the three two-electron oxidation complexes may belong to Class II-III or Class III mixed valence complexes.…”
Section: Uv-vis-nir Spectroscopymentioning
confidence: 99%
“…As shown in Figure 5 and Figure S8, each of complexes 1 – 8 exhibits two quasi‐reversible one‐electron redox processes in the positive potential range (E>0). From Table 4, the first redox potentials of 1 – 8 are close to the relevant precursors CpFe II (dppe)CN (E 1/2 =0.48 V), CpMe 4 Fe II (dppe)CN (E 1/2 =0.30 V) and CpMe 5 Fe II (dppe)CN (E 1/2 =0.25 V) [15] with a reasonable increase, respectively. Thus, they can be assigned to the redox of the CpMe n Fe II (dppe)CN fragment in 1 – 8 .…”
Section: Resultsmentioning
confidence: 59%
“…It also should be noted that the Fe−P bond length of 1 (2.1834(12) Å) are comparable to that of the precursor CpFe II (dppe)CN (2.1803(7) Å) [14] . However, the Fe−P distances of 2 (2.2115(17) Å) and 3 (2.224(2) Å) elongate by about 0.02 and 0.03 Å with respect to the precursors CpMe 4 Fe II (dppe)CN (2.1907(12) Å) and CpMe 5 Fe II (dppe)CN (2.1952(9) Å), [15] respectively, suggesting clearly the increase of oxidation state of the terminal Fe II in the order of 1 < 2 < 3 . Based on above crystallographic analysis, it can be found that the intramolecular electron interactions between the terminal Fe II and the central Ru 2 III,III exists and is enhanced by the increase of electron‐donating ability of the CpMe n ligand in complexes 1 (n=0), 2 (n=4) and 3 (n=5).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations